2009
DOI: 10.1007/s10620-009-1067-y
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Intraepithelial Eosinophils in Dysphagic Patients with Gastroesophageal Reflux Disease

Abstract: An association exists between the number of intraepithelial eosinophils and dysphagia in GERD patients, with the highest number of eosinophils in those with the primary symptom of dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In GERD patients with unexplained dysphagia, Ayazi et al, found that the number of intraepithelial eosinophils correlated with dysphagia severity. Eosinophils secrete products which antagonize muscarinic M2 receptors and cause vagal dysregulation and decreased esophageal muscle contractility, and this may be the probable mechanism of dysphagia in GERD patients [ 30 ]. In achalasia patients, neurotoxic secretory products released from eosinophils in the epithelium and the myenteric plexus may play a role in disease pathogenesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In GERD patients with unexplained dysphagia, Ayazi et al, found that the number of intraepithelial eosinophils correlated with dysphagia severity. Eosinophils secrete products which antagonize muscarinic M2 receptors and cause vagal dysregulation and decreased esophageal muscle contractility, and this may be the probable mechanism of dysphagia in GERD patients [ 30 ]. In achalasia patients, neurotoxic secretory products released from eosinophils in the epithelium and the myenteric plexus may play a role in disease pathogenesis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently Ayazi et al [12] from the famous DeMeester group in Los Angeles demonstrated a positive association between dysphagia and an increased number of intraepithelial eosinophils within biopsies obtained from GERD patients. Eosinophils represent a major source of pro-in- flammatory chemokines and growth factors, which may affect sensation and transport function of the esophagus [6].…”
Section: Dear Readersmentioning
confidence: 99%